„Oly különbségek és dolgok […] mik tulajdonképen nincsenek”: A Nova grammatica Ungarica megítélésének változásai - Bartók, István (Studia Litteraria, 2026)
Albert Szenci Molnár’s Hungarian grammar written in Latin (Novae Grammaticae Ungaricae libri duo, published in Hanau in 1610) is the first complete classification of the Hungarian language, including its syntax. It fits perfectly into the European movement toward the rise of the vernacular. Recording these rules makes it possible to express nuanced ideas in the native language as eloquently as in Latin. This contributes to the strengthening of national consciousness and the development of linguistic patriotism.